Progressões aritméticas na linha construtivista - Melo, Marcelo de Souza (2018)
This work shows how the content Arithmetic Progressions can be approached following the constructivist line of teaching, making the students have more active participation in the construction of their knowledge. It is veri_ed that using this model, one can improve students' understanding by introducing in the initial classes one or more problem situations in order to raise previous knowledge for the later acquisition of new knowledge. There are some arguments of professors / educators on this subject and also the practical application of classes structured in the constructivist line on arithmetic progressions, for students of the second year of high school in a public school in the Federal District. The observations about this style of class were made not only by the teacher who applied the activity proposed in class, but also by the students who answered questions that allowed to express the impressions about the activity.